Amorphous bismuth molybdate photocatalytic material as well as preparation method and application thereof
The modified amorphous bismuth molybdate photocatalyst was synthesized by co-precipitation, which solved the problem of low photocatalytic efficiency of crystalline bismuth molybdate and achieved efficient degradation of organic pollutants, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202510951524.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-10-28
AI Technical Summary
Existing crystalline bismuth molybdate photocatalysts suffer from problems such as high photo-electron-hole recombination rate, low quantum yield, slow photo-electron migration, and low radical conversion rate, while research on amorphous materials is relatively lacking.
Amorphous bismuth molybdate photocatalyst material was synthesized by coprecipitation method, and modified by water-soluble anionic polymers such as sodium polystyrene sulfonate to form amorphous Bi2MoO6 nanoparticles with a large specific surface area and more mesoporous structures.
The synthesis is time-saving and low-cost at room temperature and pressure, making it suitable for industrial mass production. It significantly improves the adsorption and photocatalytic degradation efficiency of Rhodamine B, achieving a degradation rate of 99%.
Smart Images

Figure CN120838401A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photocatalytic materials technology, and in particular to an amorphous bismuth molybdate photocatalytic material, its preparation method, and its application. Background Technology
[0002] Bismuth-based photocatalysts, as visible-light-responsive photocatalysts, have attracted widespread attention from researchers due to their advantages such as low cost, non-toxicity, and excellent photochemical properties. Among them, bismuth molybdate (Bi₂MoO₆) is the most representative photocatalyst, a typical and energy-rich n-type aurivillius oxide. Bi₂MoO₆ is a stable and non-toxic catalyst with a narrow band gap (2.5-2.8 eV), showing great potential in water splitting, organic pollutant degradation, and sterilization under visible light excitation. Three variants of Bi₂MoO₆ can be obtained by adjusting the pH value and the bismuth-molybdenum ratio (Bi / Mo), namely α-Bi₂Mo₃O₆... 12 Bi₂Mo₂O₉ and γ-Bi₂MoO₆ are three main photocatalysts, with γ-Bi₂MoO₆ being the most widely studied due to its non-toxicity, harmlessness, and excellent photocatalytic performance. Bi₂MoO₆ is composed of [MoO₆]. 2- Octahedral perovskite layer and [Bi2O2] 2+ Bi₂MoO₆ is composed of alternating thin layers, with its valence band forming a hybrid conduction band at the Bi-6s and O-2p levels. This unique structure exhibits excellent oxidation capabilities, efficiently degrading organic pollutants and improving the mobility and separation rate of photogenerated electrons and holes, demonstrating superior photocatalytic activity under visible light irradiation. However, the high recombination rate of photogenerated electron-hole pairs, low quantum yield, slow migration of photogenerated electrons, and low conversion rate of free radicals limit the development of Bi₂MoO₆. Therefore, researchers have proposed various improvement methods to enhance the photocatalytic activity of Bi₂MoO₆, such as morphological structure regulation, heterojunction construction, and doping modification. Furthermore, most research has focused on crystalline materials, with amorphous materials receiving little attention. Currently, research on amorphous bismuth molybdate nanomaterials for photocatalysis remains largely unexplored both domestically and internationally, making this a novel endeavor in some respects. Summary of the Invention
[0003] In view of this, this application provides an amorphous bismuth molybdate photocatalytic material, its preparation method and application. The amorphous bismuth molybdate photocatalytic material has a large specific surface area and a higher proportion of mesoporous structures, and has high-efficiency catalytic degradation performance for organic dyes, which can effectively overcome the defects of the prior art.
[0004] The first aspect of this application provides a method for preparing an amorphous bismuth molybdate photocatalytic material, comprising the following steps:
[0005] (1) Dissolve Bi(NO3)3·5H2O in HAC solution, mix and stir evenly at room temperature, and label it as solution A; dissolve Na2MoO4 in water, add water-soluble anionic polymer and stir evenly, and label it as solution B;
[0006] (2) The solution B is slowly added dropwise to the solution A, and a co-precipitation reaction is carried out under normal temperature and pressure conditions. The mixture is stirred at room temperature. After stirring is completed, the mixture is centrifuged, washed, and dried to obtain the amorphous bismuth molybdate photocatalyst material A-Bi2MoO6.
[0007] Preferably, in step (1), the water-soluble anionic polymer is sodium polystyrene sulfonate.
[0008] Preferably, in step (2), the dropping rate is 10 ml / h and the coprecipitation reaction time is 2 h.
[0009] Preferably, in step (2), the washing is performed by washing with ethanol and then with water in sequence.
[0010] Preferably, in step (2), the drying is carried out by vacuum drying, the vacuum drying temperature is 60°C, and the vacuum drying time is 2 hours.
[0011] Preferably, in step (1), the ratio of Bi(NO3)3·5H2O to HAC solution is 4 mmol: 10 ml.
[0012] Preferably, in step (1), the ratio of Na2MoO4 to water is 2 mmol: 20 ml.
[0013] The second aspect of this application also provides an amorphous bismuth molybdate photocatalyst material, A-Bi2MoO6, which is prepared by the above method.
[0014] A third aspect of this application also provides the application of the aforementioned amorphous bismuth molybdate photocatalyst in the degradation of organic pollutants, including the following steps:
[0015] The aforementioned amorphous bismuth molybdate photocatalyst material was dissolved in wastewater. Rhodamine B was selected as a simulated organic pollutant for photocatalytic degradation experiments. First, a dark reaction stage was carried out under no-light conditions. Then, after the adsorption and desorption of the dark reaction reached equilibrium, the light source was turned on at room temperature to carry out photocatalytic degradation.
[0016] Preferably, the light source is an LED lamp with a power of 100W and a wavelength of λ≥420nm; the concentration of Rhodamine B is 10mg / L; and the photocatalytic reaction time is 60min.
[0017] Compared with the prior art, this application has the following advantages:
[0018] (1) This application uses the coprecipitation method to synthesize A-Bi2MoO6 photocatalyst. The synthesis process is short, low-cost and low-energy. At the same time, it is synthesized under normal temperature and pressure conditions, which is suitable for industrial and mass production.
[0019] (2) In this application, water-soluble anionic polymers such as sodium polystyrene sulfonate are used to modify bismuth molybdate during the synthesis of amorphous bismuth molybdate. The modified amorphous A-Bi2MoO6 obtained has a larger specific surface area and more mesoporous structures than Bi2MoO6 prepared by hydrothermal treatment. This is beneficial for sensitizing Rhodamine B organic dye, enhancing the adsorption of Rhodamine B, and enabling efficient catalytic degradation of the adsorbed dye under light irradiation. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in this application or the prior art, the drawings used in the description of this application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0021] Figure 1 These are X-ray diffraction (XRD) patterns of Examples 1-4 of this application, wherein the products of Examples 1-4 are sequentially labeled as BMO-PSS1, BMO-PSS2, BMO-PSS4 and BMO-PSS8;
[0022] Figure 2 These are the X-ray diffraction (XRD) patterns of comparative examples 1-4 of this application, wherein the products of comparative examples 1-4 are labeled as BMO-0, BMO-PVP, BMO-SDBS and BMO-SDS, respectively.
[0023] Figure 3 These are scanning electron microscope (SEM) images of amorphous bismuth molybdate BMO-PSS 4 (Example 3) and amorphous bismuth molybdate BMO-0 (Comparative Example 1) of this application.
[0024] Figure 4 This is the XPS image of amorphous bismuth molybdate BMO-PSS 4 from Example 3 of this application;
[0025] Figure 5 This is a graph showing the degradation performance of Rhodamine B in a visible light catalytic system for Examples 3 and Comparative Examples 1-4 of this application;
[0026] Figure 6 These are the degradation performance diagrams of Rhodamine B in the visible light catalytic system of Examples 1-4 of this application. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0028] Unless otherwise specified, the experimental methods used in the embodiments of this application are all conventional methods.
[0029] In the following examples and comparative examples, unless otherwise specified, all raw materials can be prepared by commercial purchase or conventional methods.
[0030] Example 1
[0031] This embodiment describes a method for preparing an amorphous bismuth molybdate photocatalytic material, comprising the following steps:
[0032] (1) Weigh 1.94g of Bi(NO3)3·5H2O and dissolve it in 10ml of HAC solution. Stir on a magnetic stirrer for 30min at room temperature until it is fully dissolved. Label it as solution A.
[0033] (2) Weigh 0.488g Na2MoO4 and dissolve it in 20ml of aqueous solution. Add 1mL of sodium polystyrene sulfonate and stir on a magnetic stirrer for 30min at room temperature to ensure complete dissolution. Label this solution as solution B.
[0034] (3) Transfer the completely dissolved solution B into a 20ml syringe, place it on a syringe pump and slowly add it dropwise to solution A in step (1) at a rate of 10ml / h. During this period, keep the magnetic stirrer stirring at a constant speed to carry out the coprecipitation reaction for 2h at room temperature.
[0035] (4) After the reaction is complete, centrifuge the product, then wash it three times with ethanol and three times with water alternately, and dry it in a vacuum drying oven at 60°C for 2 hours to obtain the photocatalyst, which is named BMO-PSS1.
[0036] The XRD pattern of the product in this embodiment is as follows: Figure 1 As shown, by Figure 1 It can be seen that the diffraction peaks of the product are not obvious and the product structure is an amorphous structure. This is because no specific crystals were formed under normal temperature and pressure.
[0037] Example 2
[0038] This embodiment describes a method for preparing an amorphous bismuth molybdate photocatalytic material, comprising the following steps:
[0039] (1) Weigh 1.94g of Bi(NO3)3·5H2O and dissolve it in 10ml of HAC solution. Stir on a magnetic stirrer for 30min at room temperature until it is fully dissolved. Label it as solution A.
[0040] (2) Weigh 0.488g Na2MoO4 and dissolve it in 20ml of aqueous solution. Add 2mL of sodium polystyrene sulfonate and stir on a magnetic stirrer for 30min at room temperature until it is fully dissolved. Label it as solution B.
[0041] (3) Transfer the completely dissolved solution B into a 20ml syringe, place it on a syringe pump and slowly add it dropwise to solution A in step (1) at a rate of 10ml / h. During this period, keep the magnetic stirrer stirring at a constant speed to carry out the coprecipitation reaction for 2h at room temperature.
[0042] (4) After the reaction is complete, centrifuge the product, then wash it three times with ethanol and three times with water alternately, and dry it in a vacuum drying oven at 60°C for 2 hours to obtain the photocatalyst, which is named BMO-PSS2.
[0043] The XRD pattern of the product in this embodiment is as follows: Figure 1 As shown, by Figure 1 It can be seen that the diffraction peaks of the product are not obvious and the product structure is an amorphous structure. This is because no specific crystals were formed under normal temperature and pressure.
[0044] Example 3
[0045] This embodiment describes a method for preparing an amorphous bismuth molybdate photocatalytic material, comprising the following steps:
[0046] (1) Weigh 1.94g of Bi(NO3)3·5H2O and dissolve it in 10ml of HAC solution. Stir on a magnetic stirrer for 30min at room temperature until it is fully dissolved. Label it as solution A.
[0047] (2) Weigh 0.488g Na2MoO4 and dissolve it in 20ml of aqueous solution. Add 4mL of sodium polystyrene sulfonate and stir on a magnetic stirrer for 30min at room temperature to ensure complete dissolution. Label this solution as solution B.
[0048] (3) Transfer the completely dissolved solution B into a 20ml syringe, place it on a syringe pump and slowly add it dropwise to solution A in step (1) at a rate of 10ml / h. During this period, keep the magnetic stirrer stirring at a constant speed to carry out the coprecipitation reaction for 2h at room temperature.
[0049] (4) After the reaction is complete, centrifuge the product, then wash it three times with ethanol and three times with water alternately, and dry it in a vacuum drying oven at 60°C for 2 hours to obtain the photocatalyst, which is denoted as BMO-PSS 4.
[0050] The XRD pattern of the product in this embodiment is as follows: Figure 1 As shown, by Figure 1 It can be seen that the diffraction peaks of the product are not obvious and the product structure is an amorphous structure. This is because no specific crystals were formed under normal temperature and pressure.
[0051] SEM images of the product in this embodiment are as follows: Figure 3 As shown. Since the product is amorphous, XPS analysis was performed to further confirm whether it is bismuth molybdate, as shown. Figure 4 The valence state of the product BMO-PSS 4 shown is consistent with that of Bi2MoO6. Further XPS and SEM analysis confirm that BMO-PSS 4 is amorphous Bi2MoO6.
[0052] Example 4
[0053] This embodiment describes a method for preparing an amorphous bismuth molybdate photocatalytic material, comprising the following steps:
[0054] (1) Weigh 1.94g of Bi(NO3)3·5H2O and dissolve it in 10ml of HAC solution. Stir on a magnetic stirrer for 30min at room temperature until it is fully dissolved. Label it as solution A.
[0055] (2) Weigh 0.488g Na2MoO4 and dissolve it in 20ml of aqueous solution. Add 8mL of sodium polystyrene sulfonate and stir on a magnetic stirrer for 30min at room temperature to ensure complete dissolution. Label this solution as solution B.
[0056] (3) Transfer the completely dissolved solution B into a 20ml syringe, place it on a syringe pump and slowly add it dropwise to solution A in step (1) at a rate of 10ml / h. During this period, keep the magnetic stirrer stirring at a constant speed to carry out the coprecipitation reaction for 2h at room temperature.
[0057] (4) After the reaction is complete, centrifuge the product, then wash it three times with ethanol and three times with water alternately, and dry it in a vacuum drying oven at 60°C for 2 hours to obtain the photocatalyst, which is denoted as BMO-PSS 8.
[0058] The XRD pattern of the product in this embodiment is as follows: Figure 1 As shown, by Figure 1 It can be seen that the diffraction peaks of the product are not obvious and the product structure is an amorphous structure. This is because no specific crystals were formed under normal temperature and pressure.
[0059] Comparative Example 1
[0060] The product of this comparative example is amorphous bismuth molybdate, and its preparation process is the same as that of Example 4. The difference is that the water-soluble anionic polymer sodium polystyrene sulfonate was not added, and the resulting product is denoted as BMO-0.
[0061] The XRD pattern of this comparative example BMO-0 is as follows: Figure 2 As shown, it is an amorphous structure.
[0062] Comparative Example 2
[0063] The preparation process of the product in this comparative example is the same as that in Example 2, except that sodium polystyrene sulfonate is replaced with sodium dodecylbenzene sulfonate, and the resulting product is denoted as BMO-SDBS.
[0064] The XRD pattern of this comparative BMO-SDBS is as follows: Figure 2 As shown, it is an amorphous structure.
[0065] Comparative Example 3
[0066] The preparation process of the product in this comparative example is the same as that in Example 2, except that sodium polystyrene sulfonate is replaced with polyvinylpyrrolidone PVP-K30, and the resulting product is denoted as BMO-PVP.
[0067] The XRD pattern of this comparative BMO-PVP is as follows: Figure 2 As shown, it is an amorphous structure.
[0068] Comparative Example 4
[0069] The preparation process of the product in this comparative example is the same as that in Example 2, except that sodium polystyrene sulfonate is replaced with sodium dodecyl sulfonate, and the resulting product is denoted as BMO-SDS.
[0070] The XRD pattern of this comparative BMO-SDS is as follows: Figure 2 As shown, it is an amorphous structure.
[0071] Degradation performance
[0072] Application Example 1
[0073] The photocatalysts prepared in Example 3 and Comparative Examples 1, 2, 3, and 4 were used to conduct photocatalytic degradation experiments of Rhodamine B in a visible light catalytic system. The simulated organic pollutant was Rhodamine B, the wastewater volume was 40 ml, and the concentration of Rhodamine B was 10 mg / L. An LED lamp with a power of 100 W and λ ≥ 420 nm was used as the light source. The dark reaction took 30 min to reach adsorption-desorption equilibrium, and the light reaction took 60 min, with 4 mL samples taken every 10 min. The samples were centrifuged at 4500 rpm for 5 min and measured and recorded using a UV-Vis spectrophotometer at the maximum absorption wavelength of 554 nm. The degradation efficiency is expressed as C / C0, where C represents the sample concentration at different time points, and C0 represents the sample concentration at the initial state. Figure 5 The graph shows the degradation performance of Rhodamine B in a visible light catalytic system for Examples 3 and Comparative Examples 1, 2, 3, and 4 of this application.
[0074] Depend on Figure 5 It can be seen that, under visible light irradiation conditions, the photocatalytic performance of Example 3 on Rhodamine B is superior to that of Comparative Examples 1, 2, 3, and 4. Combined with... Figure 1 , 2 It is known that adding sodium polystyrene sulfonate does not affect the catalyst itself. Therefore, the effect of different concentrations of sodium polystyrene sulfonate on performance is further investigated.
[0075] Application Example 2
[0076] The photocatalysts prepared in Examples 1, 2, 3, and 4 above were used to conduct photocatalytic degradation experiments of Rhodamine B in a visible light catalytic system. The simulated organic pollutant was Rhodamine B, the wastewater volume was 40 ml, and the concentration of Rhodamine B was 10 mg / L. An LED lamp with a power of 100 W and λ ≥ 420 nm was used as the light source. The dark reaction took 30 min to reach adsorption-desorption equilibrium, and the light reaction took 60 min, with 4 mL samples taken every 10 min. The samples were centrifuged at 4500 rpm for 5 min and measured and recorded using a UV-Vis spectrophotometer at the maximum absorption wavelength of 554 nm. The degradation efficiency is expressed as C / C0, where C represents the sample concentration at different time points, and C0 represents the sample concentration at the initial state. Figure 6 The graphs show the degradation performance of Rhodamine B in visible light catalytic systems in Examples 1, 2, 3, and 4 of this application.
[0077] Depend on Figure 6 It can be seen that with the increase of PSS addition, the degradation of Rhodamine B by modified amorphous bismuth molybdate first increases and then decreases within a fixed time. Unmodified amorphous bismuth molybdate BMO-0 has virtually no degradation effect on Rhodamine B under light irradiation. Based on the above experimental conditions, the optimal photocatalytic conditions for an initial concentration of Rhodamine B solution of 10 mg / L are: 0.4 g / L of BWO-PSS 4 in the Rhodamine B solution, irradiated with a 100W LED lamp for 60 min, resulting in the visible photocatalytic degradation of 99% of the Rhodamine B in the solution.
[0078] In summary, this application modifies bismuth molybdate formed by co-precipitation with a water-soluble anionic polymer such as sodium polystyrene sulfonate, resulting in amorphous Bi₂MoO₆ nanoparticles with a larger specific surface area and more mesoporous structures. The elemental composition and valence state of Bi₂MoO₆ were confirmed through structural characterization. Its performance was evaluated by photocatalytic degradation of Rhodamine B solution; the degradation rate of Rhodamine B reached 99% after 60 minutes of light irradiation. This provides valuable reference for the modification of amorphous semiconductor materials.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing an amorphous bismuth molybdate photocatalyst, characterized in that, Includes the following steps: (1) Dissolve Bi(NO3)3·5H2O in HAC solution, mix and stir evenly at room temperature, and label it as solution A; dissolve Na2MoO4 in water, add water-soluble anionic polymer and stir evenly, and label it as solution B; (2) The solution B is slowly added dropwise to the solution A, and a co-precipitation reaction is carried out under normal temperature and pressure conditions. The mixture is stirred at room temperature. After stirring is completed, the mixture is centrifuged, washed, and dried to obtain the amorphous bismuth molybdate photocatalyst material A-Bi2MoO6.
2. The method for preparing the amorphous bismuth molybdate photocatalyst material according to claim 1, characterized in that, In step (1), the water-soluble anionic polymer is sodium polystyrene sulfonate.
3. The method for preparing the amorphous bismuth molybdate photocatalyst material according to claim 1, characterized in that, In step (2), the dropping rate is 10 ml / h and the coprecipitation reaction time is 2 h.
4. The method for preparing the amorphous bismuth molybdate photocatalyst material according to claim 1, characterized in that, In step (2), the washing is carried out by washing with ethanol and then with water in sequence.
5. The method for preparing the amorphous bismuth molybdate photocatalyst material according to claim 1, characterized in that, In step (2), the drying is carried out by vacuum drying, the vacuum drying temperature is 60℃, and the vacuum drying time is 2h.
6. The method for preparing the amorphous bismuth molybdate photocatalyst material according to claim 1, characterized in that, In step (1), the ratio of Bi(NO3)3·5H2O to HAC solution is 4 mmol: 10 ml.
7. The method for preparing the amorphous bismuth molybdate photocatalyst material according to claim 1, characterized in that, In step (1), the ratio of Na2MoO4 to water is 2 mmol: 20 ml.
8. An amorphous bismuth molybdate photocatalyst material, characterized in that, Amorphous bismuth molybdate photocatalyst A-Bi2MoO6 was prepared by the method described in any one of claims 1-7.
9. The application of the amorphous bismuth molybdate photocatalyst material according to claim 8 in the degradation of organic pollutants, characterized in that, Includes the following steps: The amorphous bismuth molybdate photocatalytic material described in claim 8 was dissolved in wastewater. Rhodamine B was selected as a simulated organic pollutant for photocatalytic degradation experiments. First, a dark reaction stage was carried out under no-light conditions. Then, after the adsorption and desorption of the dark reaction were balanced, the light source was turned on at room temperature to carry out photocatalytic degradation.
10. The application of the amorphous bismuth molybdate photocatalyst material according to claim 9 in the degradation of organic pollutants, characterized in that, The light source is an LED lamp with a power of 100W and a wavelength of λ≥420nm; the concentration of Rhodamine B is 10mg / L; and the photocatalytic reaction time is 60min.